2000
DOI: 10.1002/(sici)1097-0290(20000620)68:6<602::aid-bit3>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of metabolic flux analysis for the identification of metabolic bottlenecks in the biosynthesis of penicillin-G

Abstract: A detailed stoichiometric model was developed for growth and penicillin‐G production in Penicillium chrysogenum. From an a priori metabolic flux analysis using this model it appeared that penicillin production requires significant changes in fluxes through the primary metabolic pathways. This is brought about by the biosynthesis of carbon precursors for the β‐lactan nucleus and an increased demand for NADPH, mainly for sulfate reduction. As a result, significant changes in flux partitioning occur around four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 60 publications
6
131
0
1
Order By: Relevance
“…For all cultivations, including the ones with the constructed strains, steady states with regard to biomass were achieved (data not shown) and the biomass yields were comparable with yields found in previous studies (van Gulik et al, 2000;Robin et al, 2003c). The specific productivities of the reference strains were estimated to be 17(±2) mmol b-lactam (g dry wt)…”
Section: Physiological Characterizationsupporting
confidence: 85%
“…For all cultivations, including the ones with the constructed strains, steady states with regard to biomass were achieved (data not shown) and the biomass yields were comparable with yields found in previous studies (van Gulik et al, 2000;Robin et al, 2003c). The specific productivities of the reference strains were estimated to be 17(±2) mmol b-lactam (g dry wt)…”
Section: Physiological Characterizationsupporting
confidence: 85%
“…A general problem is the ATP-balance which contains uncertain ATP stoichiometric parameters (P/O ratio, unknown growth related ATP ð¼ K X Þ and the unknown growth unrelated ATP ðm ATP Þ. Van Gulik and Heijnen [7] and Van Gulik et al [8] have shown how in vivo values for these ATP-parameters can be obtained using extensive experiments. For many organisms this ATP-information is not available.…”
Section: Thermodynamic Approach To Obtain Network Stoichiometry and Fmentioning
confidence: 99%
“…A very nice example is the model for penicillin production [8,16] and the model developed for biological P-removal using mixed cultures in a cyclic process [17]. These black box models show that highly complex biological systems, comprising thousands of reactions, can be effectively modeled with a reduced model containing only about 6-12 parameters.…”
Section: Black Box Models For Design Of Biotechnological Processes: Fmentioning
confidence: 99%
“…The standard for detailed physiological characterization was set in the late 1990s and is exemplified in studies that employ different cultivation modes to study various physiological states. [56][57][58] Such studies provided highly reproducible data on growth rates, yield coefficients, and productivity, allowing an assessment of conditions for optimal cellular performance.…”
Section: Improving Cell Factoriesmentioning
confidence: 99%